Ediacaran to lower Cambrian basement in eastern George V Land (Antarctica): Evidence from U Pb dating of gneiss xenoliths and implications for the South Australia- East Antarctica connection - Lamarque, Gaelle; Bascou, Jerome; Menot, Rene-pierre; Paquette, Jean-louis; Couzinie, Simon; Rolland, Yann; Cottin, Jean-yves (Lithos, 2018)
This study presents the first geochronological results on basement rocks from the Penguin-Bage-Webb (PBW) domain located east of the Neoarchean-Paleoproterozoic Terre Adélie craton, Antarctica. Investigated samples are paragneiss xenoliths hosted within early Paleozoic granitoids, which were emplaced during the Ross orogeny. Zircon UPb dating yielded ages ranging from the Archean to the Cambrian, with a dominant Ediacaran (550–635 Ma) population and maximum depositional ages around 570–575 Ma. U–Th–Pb analyses of monazite suggest that the metamorphic event that formed the gneiss samples occured at ca. 515 Ma, shortly prior to incorporation within the granitic magmas. The studied samples likely represent relics of the pre-Gondawana Pacific margin, which was subsequently deformed and metamorphosed during the early Paleozoic Ross orogeny. The obtained zircon UPb date distributions present similarities with those of the Kanmantoo and Nargoon sediments in Southern Australia and provide new constrains for the correlations between East Antarctica and South Australia before the opening of the Southern Ocean.